PENGARUH PENGGUNAAN SAMPAH ORGANIK DAN CACING TANAH (Lumbricus rubellus) TERHADAP SIFAT KIMIA DAN BIOLOGI PUPUK KASCING - Ditamulia Slamet Utama; I Made Sudana; Ni Luh Kartini (Journal of Agricultural Science and Biotechnology, 2017)
The use of agricultural land without organik fertilizers can decrease soil organik matter and decrease soil productivity. Production of organik fertilizer with natural composting process will be take a long time. The addition of earthworm (Lumbricusrubellus) on organik materials can accelerate the composting process. Vermicompost has a lot of plant growth hormones, beneficial microbes, and plant nutrients. Research purposes were to determine the effectiveness of earthworms to decompose the organic matter, to determine the weight earthworms are able to accelerate the decomposition of organic waste into fertilizer, and to determine the biological and chemical fertilizers produced from organic waste with earthworms compared without earthworms. The research method used a randomized block design 2 factorial. The variables measured were the weight of earthworms, the decomposition effectiveness, quality of fertilizers and fertilizer application in mustard. The data was analyzed by analysis of variance, if there was a significant interaction effect of the variable followed by Duncan's multiple range test, and if the only real effect of a single factor followed by LSD test.The result show that the earthworm effective in the decomposition of organic waste into vermicompost fertilizer. Increasingly the weight of the earthworm the process of decomposition organic material into vermicompost fertilizer more quickly,the best treatment for the decomposition of organic matter was C3B1, C3B2, and C3B3. Biological and chemical character of fertilizer produced from organic waste with earthworms is better than without earthworms. The best treatment was C1B3.